Toxicogenetic study of omeprazole and the modulatory effects of retinol palmitate and ascorbic acid on Allium cepa. (August 2018) - Braga, Antonio Lima; de Meneses, Ag-Anne Pereira Melo; Santos, José Victor de Oliveira; dos Reis, Antonielly Campinho; de Lima, Rosália Maria Tôrres; da Mata, Ana Maria Oliveira Ferreira; Paz, Márcia Fernanda Correia Jardim; Alves, Leane Brunelle dos Santos; Shaw, Subrata; Uddin, Shaikh Jamal; Rouf, Razina; Das, Asish Kumar; et al.
Abstract: Omeprazole (OME) is a proton pump inhibitor used for the treatment of various gastric and intestinal disease; however, studies on its effects on the genetic materials are still restricted. The present study aimed to evaluate possible toxicogenic effects of OME in Allium cepa meristems with the application of cytogenetic biomarkers for DNA damage, mutagenic, toxic and cytotoxic effects. Additionally, retinol palmitate (RP) and ascorbic acid (AA) were also co-treated with OME to evaluate possible modulatory effects of OME-induced cytogenetic damages. OME was tested at 10, 20 and 40 μg/mL, while RP and AA at 55 μg/mL and 352.2 μg/mL, respectively. Copper sulphate (0.6 μg/mL) and dechlorinated water were used as positive control and negative control, respectively. The results suggest that OME induced genotoxicity and mutagenicity in A. cepa at all tested concentrations. It was noted that cotreatment of OME with the antioxidant vitamins RP and/or AA significantly (p < 0.05) inhibited and/or modulated all toxicogenic damages induced by OME. These observations demonstrate their antigenotoxic, antimutagenic, antitoxic and anticitotoxic effects in A. cepa . This study indicates that application of antioxidants may be useful tools to overcome OME-induced toxic effects. Highlights: Omeprazole induced toxic, cytotoxic, genotoxic and mutagenic effects in Allium cepa. Retinol palmitate and ascorbic acid inhibited/modulated omeprazole's activity. Antioxidant vitamins during omeprazole-mediated toxicity.